2019
DOI: 10.3390/catal9110933
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Metal Oxide–Support Interactions on Ethylene Oligomerization over Nickel Oxide/Silica–Alumina Catalysts

Abstract: We investigated the interactions between nickel oxide and silica–alumina supports, which were applied to the catalytic oligomerization of ethylene by powder X-ray diffraction, UV diffuse reflectance spectroscopy, H2 temperature-programmed reduction, and X-ray photoelectron spectroscopy. The catalytic activity was also correlated with the acidity of catalysts determined by NH3 temperature-programmed desorption and pyridine FT-IR spectroscopy. Although all the catalysts had similar Ni contents, their catalytic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 73 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…Since nickel naturally oxidizes, such oxidation-related peaks appear for Ni Nps. The results of previous studies support the assignment of BEs of 852.6, 855-856, and 857-858 eV in the Ni 2P 3/2 XPS spectra for Ni0, Ni 2+ , and Ni 3+ in oxidized Ni, oxides, and hydroxides and oxyhydroxides, respectively[27][28][29]. The BE of 860.2 eV is characteristic of related satellite peaks.…”
supporting
confidence: 80%
“…Since nickel naturally oxidizes, such oxidation-related peaks appear for Ni Nps. The results of previous studies support the assignment of BEs of 852.6, 855-856, and 857-858 eV in the Ni 2P 3/2 XPS spectra for Ni0, Ni 2+ , and Ni 3+ in oxidized Ni, oxides, and hydroxides and oxyhydroxides, respectively[27][28][29]. The BE of 860.2 eV is characteristic of related satellite peaks.…”
supporting
confidence: 80%
“…However, reflections at 37.2°, 43.3°, and 62.9° corresponding to the (111), (200), and (220) planes of the NiO phase (JCPDS 04-0835) are perceived only in the PM-2.5% (2.5 wt% Ni) catalysts. 10,22,30 This result indicates that the Ni in IWI-2.5% (2.5 wt% Ni) and IE-2.5% (2.5 wt% Ni) samples shows good dispersibility in the carrier. Meanwhile, the uniform distribution of Ni can effectively avoid the deactivation of the catalyst due to the sintering effect, 31 thereby promoting the stability and reaction activity of the catalyst.…”
Section: Resultsmentioning
confidence: 87%
“…However, the effects of Ni site distributions for ethylene oligomerization have rarely been studied. [21][22][23] How to control and describe the Ni site distribution? Some reference studies reported methods for controlling the location of metals (Pt, Pd, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…MgO impregnated Al 2 O 3 was investigated in the catalytic decomposition of hydrofluorocarbon, which confirmed that the weak Lewis acid site of Al 2 O 3 and basic sites of Mg were advantageous for the high activity and catalyst lifetime [22]. NiO was also supported on SiO 2 -Al 2 O 3 support via metal oxide-support interaction, in which the medium interaction strength preserving the active nickel oxides and acid sites was important for achieving optimal catalytic activity in ethylene oligomerization [23]. Pt metal nanoparticle embedded Co-based metal organic framework was pyrolyzed to porous carbon Pt@Co/C composite, which could be used as the Fischer-Tropsch catalyst achieving 35% CO conversion with various hydrocarbons at low pressure [24].…”
mentioning
confidence: 79%